2023
DOI: 10.1021/acsomega.3c00699
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Elemental Impurity Analysis of Heterogeneous Morphologies in Uranium Oxides Synthesized from Uranyl Fluoride Precursors

Abstract: The surface morphology characteristics of postenrichment deconversion products in the nuclear fuel cycle are important for producing nuclear fuel pellets. They also provide the first opportunity for a microstructural signature after conversion to gaseous uranium hexafluoride (UF 6 ). This work synthesizes uranium oxides from uranyl fluoride (UO 2 F 2 ) starting solutions by the wet ammonium diuranate route and a modification of the dry route. Products are reduced under a nitrogen/hydrogen atmosphere, with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 47 publications
(114 reference statements)
1
31
0
Order By: Relevance
“…The other half of the UO 2 F 2 was directly dried and again split in half for reductions with or without steam. 19 Reduction of MDU, ADU, and UO 2 F 2 to UO x . The reduction of MDU, ADU, and UO 2 F 2 to UO x was reported previously.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The other half of the UO 2 F 2 was directly dried and again split in half for reductions with or without steam. 19 Reduction of MDU, ADU, and UO 2 F 2 to UO x . The reduction of MDU, ADU, and UO 2 F 2 to UO x was reported previously.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The average water vapor concentration in a 50 mL min −1 wet N 2 stream coupled with a 440 mL min −1 dry UHP N 2 stream was 5240 ± 40 ppm, analyzed by cavity ring down spectroscopy (CRDS) measurements taken over 30 min. 19 For a flow of 60 mL•min −1 , the water vapor concentration was 6290 ± 50 ppm; 19 the δ 18 O value of the water vapor was −25.11 ± 0.36‰. 19 We did not measure the δ 18 O value of the liquid water from which the vapor was generated; however, 13 tap water samples collected between 2013 and 2023 from the University of Utah campus near the lab discussed herein have an average δ 18 O value of −15.86‰ (±0.41‰) (waterisotopes.org, projects 00058, 00059, 00064).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Controlling particle morphology is of great importance to many industries including semiconductors, nanomaterials, and steel fabrication. Levlev et al showed that a mechanistic understanding of nucleation and growth mechanisms can lead to improved modeling of material properties and future material discovery . In the nuclear industry, particle morphology can impact the environmental transport of uranium, nuclear fuel performance in reactors, long-term storage of spent nuclear fuel, and support nuclear forensics and nuclear safeguards in identifying the processing history of nuclear materials. ,, Prior studies have identified many variables including pH, temperature, reaction time, and calcination temperature that impact the final particle morphology. Advancements in particle segmentation and machine learning enable quantification of even subtle morphology changes. , The challenge, however, has been in understanding the fundamental principles that result in unique particle morphologies based on the chemical and physical processing conditions. In situ liquid phase transmission electron microscopy can help reveal the underlying mechanisms of particle formation, particularly when the impacts of radiolysis can be mitigated. , In the case of studtite, electron beam radiolysis of uranyl solutions enables the controlled in situ precipitation of particles under different reaction conditions.…”
Section: Introductionmentioning
confidence: 99%